Developing a strength-power program for amateur boxing - Ebben, W. P.; Blackard, D. O. (Strength and Conditioning Journal, 1997)
MISCONCEPTIONS ABOUT THE principles of strength and conditioning have fostered several myths concerning the physical preparation of amateur boxers. This is especially true for those who are taught some of the old training techniques from some boxing coac hes. While boxing coaches are experienced in tactical preparation and dedicated to the sport, they vary in their knowledge of physical preparation. Several studies have indicated the benefits of strength and conditioning for amateur boxers (2-4, 9, 16, 17, 19), but it takes time for the results of research to reach the amateur boxing community. This article reviews popular weight room myths we have heard from amateur boxers at the U.S. Olympic Education Center (USOEC) at Northern Michigan University in Marquette. These myths are challenged and an appropriate strength-power training program for amateur boxers is presented. Physical Fitness Evaluation Before a strength-power training program is developed, baseline measurements should be obtained to identify one's strengths and weaknesses. A fitness evaluation verifies personal achievement, stimulates research, motivates the athlete, and determines the effectiveness of a strength and conditioning program ( 14). Fitness evaluations are conducted at the USOEC for each resident athlete. Data are collected on age, sex, height, weight, heart rate, blood pressure, body girths, body composition, flexibility, aerobic endurance, agility, and muscular power, strength, and endurance. Body composition is assessed via skinfold calipers. Flexibility is assessed with a go'niometer. Aerobic endurance is assessed through a 1 -mile run, the McArdle step test, or YMCA submaximal bicycle test. Agility is assessed by the Edgren side-step test. Muscular power is assessed with the verticaT''' jump and the medicine ball vertical put. Muscular strength and endurance are measured by a 5-RM test of the squat, bench press, and hip sled, a l-min sit-up and push-up test, and an RM bench press test at 75% body weight. During their fitness evaluations and while participating in the prograrn, the athletes often express their beliefs about strength-power programs for boxing. Many of these beliefs are based on myths. These myths are refuted during the athletes' physical fi tness evaluation and throughout their participation in the strength and conditioning program. The Myths Myth 1: Weight training decreases Flexibility. It has been assumed that weight training results in athletes being "muscle bound and less flexible.